Synthesis and Physiological Activities of Some Imines and Their ?-Lactams - M. Nair, Soumya; Bhattacharya, Ira (Asian Journal of Chemistry, 2010)
The compounds 4-[N-(4-nitro phenyl) methylidinyl] resorcinol (I), 4-[N-(4-methyl phenyl)methylidinyl]resorcinol (II), 4-[N-(4-methoxy phenyl) methylidinyl]resorcinol (III), 4-[N-(4-chloro phenyl)methylidinyl]resorcinol (IV) and 4-[N-(4-bromo phenyl) methylidinyl]resorcinol (V) have been synthesized by refluxing resorcinol and p-chloro aniline with triethylorthoformate. The products formed were further used to prepare their respective β-lactams 3-(chloro)-4-[(2,4-dichloroacetoxy) phenyl]-1-(4-nitro phenyl)azetidin-2-one (VI), 3-(chloro)-4-[(2,4-dichloroacetoxy)phenyl]-1-(4-methyl phenyl)azetidin-2-one (VII), 3-(chloro)-4-[(2,4-dichloroacetoxy) phenyl]-1-(4-methoxy phenyl)azetidin-2-one (VIII), 3-(chloro)-4-[(2,4-dichloroacetoxy)phenyl]-1-(4-chloro phenyl)azetidin-2-one (IX) and 3-(chloro)-4-[(2,4-dichloroacetoxy) phenyl]-1-(4-bromo phenyl)azetidin-2-one (X) by using chloroacetylchloride and dry triethylamine. The compounds have been characterized on the basis of elemental and spectral data and screened for their antimicrobial activity.